Impacts of Solar Energy Rural Electrification in Bayomen-Cameroon - Awah Paschal (Journal of Multidisciplinary Science, 2023)
The impacts of solar energy in Bayomen-Cameroon are enormous, the implementation of a concentrated solar photovoltaic system as a source of power in the Bayomen village, centre region of Cameroon has rapidly transformed the area. In our methodology, we used qualitative data collection and analysis. Techniques like; in-depth interviews, focus group discussions, photographs and direct observations were explored with the inhabitants of the Bayomen village to understand the effects brought about by solar energy in Bayomen. The results show improvements and significant impact on education, infrastructure, trade and commerce, entertainment, health; as a result of supply of power from solar photovoltaic power plants. The system also shows more advantages on consideration of its environmental effects. A great potential for dissemination of solar technology in non-electrified rural areas exists, however, a clear and pragmatic government policy supporting solar power utilization is needed for a sustainable development of solar technology. Consequently the introduction of solar energy in the village has made people to gain the status of a business centre in the Kon-Yambettar Subdivision. Another area of study could be done on the resistances encountered by the rural electrification solar energy project in Bayomen-Cameroon.